Dried blood spot validation of five immunosuppressants, without hematocrit correction, on two LC–MS/MS systems. (April 2017) - Koster, Remco A; Veenhof, Herman; Botma, Rixt; Hoekstra, Alle Tjipke; Berger, Stefan P; Bakker, Stephan JL; Alffenaar, Jan-Willem C; Touw, Daan J
Aim: Hematocrit (Ht) effects remain a challenge in dried blood spot (DBS) sampling. The aim was to develop an immunosuppressant DBS assay on two LC–MS/MS systems covering a clinically relevant Ht range without Ht correction.Results: The method was partially validated for tacrolimus, sirolimus, everolimus, cyclosporin A and fully validated for mycophenolic acid on an Agilent and Thermo LC–MS/MS system. Bias caused by Ht effects were within 15% for all immunosuppressants between Ht levels of 0.23 and 0.48 l/l. Clinical validation of DBS versus whole blood samples for tacrolimus and cyclosporin A showed no differences between the two matrices.Conclusion: A multiple immunosuppressant DBS method without Ht correction, has been validated, including a clinical validation for tacrolimus and cyclosporin A, making this procedure suitable for home sampling.